Workshop Pembuatan Power Point Dengan Animasi di Smp Negeri 3 Kota Bengkulu - Regita Cahyaning Yutisari; Hadi Purnomo; Tari Juita Sapitri; Nurul Ichsan (JURNAL ABDIMAS SERAWAI, 2022)
Lack of expertise is one of the causes of the lack of maximum use of technology for teachers. This training aims to make the teacher council able to make teaching activities more interesting for students. It was carried out not only for new teachers but also with senior teachers under the supervision of WA Student Affairs at SMP Negeri 3 Bengkulu City. The method used in this problem is by holding a workshop on making power points using animation. This workshop was held at SMP Negeri 3 Bengkulu City which was attended by approximately 20 teachers. A face-to-face workshop by the service team, explaining step by step and opening a question and answer session during the workshop. The stages carried out in this workshop are: preparation, implementation of activities, follow-up and consultation. Consultation for teachers can be done by coming to the secretariat of the service team (school prayer room). The results of the workshop activities are so that teachers can improve work efficiency by using power points and of course add new skills to teachers